APPLICATION OF BASIC PACTA SUNT SERVANDA IN COOPERATION AGREEMENT BETWEEN PT SURYA CIPTA SWADAYA AND PT LAMPIRI DJAYA ABADI - Swandaru, Danang (Sekolah Tinggi Ilmu Hukum Awang Long, 2021)
The principle of pacta sunt servanda is also called the principle of legal certainty. This principle relates to covenant consequences. The principle of pacta sunt servanda underlines that the judge or third party must respect the substance of the contract made by the parties, as befits a law. The problem in this research is how is the application of the pacta sunt servanda principle in the cooperation agreement between PT Surya Cipta Swadaya and PT Lampiri Djaya Abadi? The research method used is normative juridical using secondary data and analyzed using qualitative methods. The results show that the application of the pacta sunt servanda principle in the cooperation agreement between PT Surya Cipta Swadaya and PT Lampiri Djaya Abadi did not occur. This is due to the absence of fine sanctions given to PT Lampiri Djaya Abadi for default, even though PT Lampiri Djaya Abadi has been proven to have defaulted. Apart from that, the failure to realize the pacta sunt servanda is due to the agreement Number 016 / SCS-EDM / SPP / XI / 2019 concerning repair work / overlay of Surya Utama (Segment 3) Phase I and Surya Utama (Segment 4) Phase II roads between PT. Lampiri Djaya Abadi with PT Surya Cipta Swadaya was made in an underhand agreement, so that no party controls or explains the contents of article by article in the cooperation agreement.